Effect of short inter-pregnancy interval on perinatal and maternal outcomes among pregnant women in SSA 2023: Systematic review and meta-analysis. - Fentahun Yenealem Beyene; Kihinetu Gelaye Wudineh; Simachew Animen Bantie; Azimeraw Arega Tesfu (PLoS ONE)
Background After a live birth, the recommended interval before attempting the next pregnancy is at least 24 months (birth to pregnancy interval) in order to reduce the risk of adverse maternal, perinatal and infant outcomes. Short inter pregnancy interval associated with adverse perinatal and maternal outcomes. Objective The objective of this review was to determine the effect of short inter pregnancy interval on perinatal and maternal outcomes in Sub-Saharan Africa 2023. Methods A systematic and a comprehensive literature searching mechanism were used without any restriction, through Google scholar, PubMed, Scopus, Web of Sciences, and Grey literature databases for reporting the effect of short inter pregnancy interval. The JBI approach to critical appraisal, study selection, data extraction, and data synthesis was used for this review. All statistical analyses were done using STATA version17 software for windows, and meta-analysis was used with a random-effects method. The results are presented using texts, tables and forest plots with measures of effect and 95% confidence interval. Results Thirteen studies were included in this review and most of the studies level of heterogeneity across the study was considerable, mainly due to methodological variations, Statistical heterogeneity, and population and intervention variations of included studies. The effect of short inter pregnancy interval on perinatal and maternal outcome were low birth weight(RR (RR (95% CI) 1.98 (1.48, 2.47); I2:62.97%, preterm birth (RR (95% CI) 1.67 (1.31, 2.03); I2:51%, intra uterine growth retardation(RR (95% CI) 3.78 (2.07, 5.49); I2: 8.52%, low APGAR score(RR (95% CI) 3.49 (1.41, 5.57)); I2: 71.11%, premature rapture of membrane(RR (95% CI) 2.87 (1.22, 4.51)); I2: 49.22%, perinatal mortality(RR (95% CI) 2.95 (1.10, 4.81)); I2: 54.37% and maternal anemia(RR (95% CI) 3.06 (2.12, 3.99)); I2: 74.74%. Conclusions As per our review the main effect of short inter pregnancy interval is low birth weight, preterm birth, intra uterine growth retardation, low APGAR score, premature rapture of membrane, perinatal mortality and maternal anemia. This might be very useful for healthcare policymakers and NGOs to emphasize on it.